Assinaturas de expansão populacional durante o Último Máximo Glacial revelam uma nova hipótese de diversificação para Akodon cursor (Rodentia, Cricetidae) - Cruz, Letícia Rosário (2023)
The neotropical rodent Akodon cursor (Winge, 1887) shows distinctive features. The species has a broad distribution throughout the Brazilian Atlantic Forest, ranging from Paraíba state in the north to Paraná in the south. There are records of 28 distinct karyotypes, with three diploid numbers (2n=14, 15, and 16) and morphological variation in 5 autosomal pairs, with a fundamental number (NF) ranging from 18 to 27. Molecular studies reveal a phylogeny with a north-south break coinciding with the region of the Jequitinhonha River. Although some localities show evidence of exclusive karyotypes, such as in Pernambuco (2n=16) and Espírito Santo (2n=14), the karyotypes are distributed in both the northern and southern clades. The species lacks significant intraspecific morphological variation, being considered cryptic with two species (A. montensis and A. diauarum), which is named as the cursor species group. These unique characteristics make this rodent an excellent model for diversification processes studies, specially within complex and heterogeneous biome as the Atlantic Forest. The role of chromosomes, rivers as geographical barriers, and climate changes bring questions about the diversification processes of this species. In this study, we investigated evolutionary events that have played a significant role in the diversification processes observed in the phylogeographic studies of A. cursor. We used a comprehensive sample of 389 specimens collected throughout the species' entire geographic range. Using mitochondrial and nuclear markers, we conducted integrative analyses such as phylogenies, Analysis of Molecular Variance (AMOVA), neutrality tests, demographic history, Bayesian Skyline Plots (BSPs) coalescent analyses, and species distribution models. Our results revealed a new phylogenetic structure, exhibiting three main clades with high support, corresponding to the northern (Paraíba, Pernambuco, northern Minas, and Bahia), central (Espírito Santo, southern Minas Gerais, and Rio de Janeiro), and southern (Espírito Santo, São Paulo, and Rio de Janeiro) regions of the Atlantic Forest.AMOVA results demonstrated that most of the genetic differentiation is attributed to differences among the three phylogroups rather than between populations located above and below the Jequitinhonha River. Neutrality tests and BSPs indicated that populations underwent demographic expansion during the Last Glacial Maximum (LGM). These results were consistent with species distribution models, showing that suitability areas for the species expanded during the same period. Additionally, spatiotemporal analysis revealed that the species originated approximately 800 thousand years ago and showed simultaneous dispersal routes to the north and south (later diverging into central and southern lineages) of the Atlantic Forest. Thus, our data support refuting the hypothesis that rivers have acted as effective barriers in the species' diversification. Instead, the expansion and contraction of suitable areas, associated with recovered demographic history patterns, suggest that Quaternary climate oscillations played a more crucial role in shaping the diversification of A. cursor. These patterns align with the predictions of the "Mata Atlantida" hypothesis, showing that expansions of suitable areas during glacial periods, especially along the continental shelf, played a crucial role in the evolutionary history of species. Furthermore, the dispersal patterns recovered by spatiotemporal dynamics also bring new insights into the origin and distribution of karyotypic variations, which seem to have occurred in the base of this rodent's diversification. Finally, although we did not find strong support for subdividing the taxon into two species, the complexity of its evolutionary history suggests that A. cursor is undergoing an early stage of speciation.